2015
DOI: 10.1515/ap-2015-0061
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and ultrastructure of Myxobolus cf. cuneus, a parasite of patinga hybrid and Henneguya pseudoplatystoma, a parasite of pintado hybrid

Abstract: Through morphological, histopathological and ultrastructural analysis of Myxobolus cuneus Adriano, Arana et Cordeiro, 2006 and Henneguya pseudoplatystoma Naldoni, Arana, Maia, Ceccarelli, Tavares, Borges, Pozo et Adriano, 2009 were identified infecting pacu respectively (Piaractus mesopotamicus) and hybrid pintado (Pseudoplatystoma corruscans x Pseudoplatystoma reticulatum) taken from Brazilian fish farms. The present study describes 18S rDNA sequencing of Myxobolus cf. cuneus infecting the spleen of farmed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…When compared to the Henneguya spp. available at the NCBI, the sequence of H. pseudoplatystoma identified in this study, demonstrated 99.6% identity with H. pseudoplatystoma collected from a hybrid surubim (P. corruscans x P. reticulatum) in São Paulo, Brazil (Milanin et al, 2015). Phylogenetic tree constructed, demonstrated that Henneguya species tend to form clades based on the family of the host fish.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…When compared to the Henneguya spp. available at the NCBI, the sequence of H. pseudoplatystoma identified in this study, demonstrated 99.6% identity with H. pseudoplatystoma collected from a hybrid surubim (P. corruscans x P. reticulatum) in São Paulo, Brazil (Milanin et al, 2015). Phylogenetic tree constructed, demonstrated that Henneguya species tend to form clades based on the family of the host fish.…”
Section: Discussionmentioning
confidence: 54%
“…3). On the other hand, species grouped in clade, E were identified as parasitizing the Pimelodidae family members in Brazilian territory, including in the southeast and central-western regions (Naldoni et al, 2011;Adriano et al, 2012;Carriero et al, 2013;Milanin et al, 2015), as well as a single parasite that was isolated in the family Naididae. At last, clade F grouped two families of fish Mugilidae and Naididae.…”
Section: Discussionmentioning
confidence: 99%
“…Até o momento, foram descritas 140 de espécies de mixosporídeos, conhecidas por parasitarem peixes de água doce brasileiras de diferentes bacias hidrográficas (ADRIANO & OLIVEIRA, 2018;OKAMURA et al, 2018) e algumas, infectando peixes nativos amplamente cultivados em pisciculturas (ADRIANO et al, 2005a(ADRIANO et al, , 2005b2009a;2009b;EIRAS et al, 2009;MARTINS & SOUZA, 1997;MARTINS, 1997;NALDONI et al, 2009;. Muitas destas descrições foram realizadas por pesquisas desenvolvidas no Laboratório de Imunologia de Parasitas da FZEA-USP (ADRIANO et al, 2005a(ADRIANO et al, , 2005b(ADRIANO et al, , 2006(ADRIANO et al, , 2009(ADRIANO et al, , 2012CAPODIFOGLIO et al,2015CAPODIFOGLIO et al, , 2016CAPODIFOGLIO et al, e 2019CARRIERO 2013;MILANIN et al, 2010MILANIN et al, , 2015a2015b;2018a;MOREIRA et al, 2014;NALDONI et al, 2011NALDONI et al, , 2014NALDONI et al, , 2015.…”
Section: Estudos Da Classe Myxosporea No Brasilunclassified
“…Utilizar as técnicas cPCR e qPCR para o diagnóstico de mixosporídeos em amostras de água de pisciculturas. Estas localidades foram escolhidas devido ao fato de que já foram identificados, anteriormente, peixes e oligoquetas infectados por mixosporídeos, como descritos nos trabalhos de Carriero et al, 2011;Milanin et al,2015aMilanin et al, , 2016Moreira et al, 2013. Por esse motivo, as amostras de água coletadas nas pisciculturas foram identificadas como amostras suspeitas.…”
Section: Objetivo Geralunclassified